Intervenciones de enfermería y su relación con la prevención de las complicaciones del pie diabético en adultos de 40 a 60 años. Hospital León Becerra Camacho, Milagro. Guayas. Mayo - septiembre 2019 - Aguilera Bueno, Yanaina Yuleysi (2019)
Introduction. The most frequent complications in patients with type 2 diabetes mellitus, take place by macrovascular and microvascular damage. Within the first stand of diabetic foot injuries that are very serious and disabling mainly in adults with years of evolution of the disease. Objective. Determine the relationship between the nursing interventions and prevention of the complications of diabetic foot in adults from 40 to 60 years who are treated at hospital León Becerra Camacho in the canton miracle of the province of Guayas in the period from May to September of 2019. Methodology. It was field, exploratory, descriptive, cross-sectional study, from a qualitative and quantitative approach. Used sampling was intentional non-probability being constituted the sample by 52 patients who had lesions typical of the diabetic foot. The technique of non-structured and direct scientific observation as well as the survey was applied. The instrument was the questionnaire. Results. Of the total sample prevailed male (65.0%). Showed that beginning at age 10 after diagnosed disease, appeared in 87% diabetic foot injuries. 28.8% of the patients, the ulcers were infected. He was obtained that the 69, 0% of the nursing staff, did the training of prevention for the complications of diabetic foot. Conclusions. It is essential to improve the quality and frequency of the nursing interventions on function of preventing the complications of diabetic foot.